Positive partnerships : a toolkit for the greater involvement of people living with or affected by HIV and AIDS in the Caribbean education sector (UNESCO KingstonJM, 2010)
Aims to assist education sector staff, networks of people living with HIV, and others to apply the principles for the greater involvement of people living with or affected by HIV and AIDS (GIPA) in a comprehensive approach for the education sector's response to HIV and AIDS.
Keywords: HIV